Sulfentrazone: Environmental Dynamics and Selectivity - GEHRKE,V.R. (2020)
ABSTRACT: Sulfentrazone is a pre-emergence herbicide that inhibits protoporphyrinogen oxidase (Protox). Its use has emphasis on areas like soybeans planted in lowlands, soybean, and sugarcane in areas of cerrado, and also in the implementation of eucalyptus afforestation. The use of sulfentrazone into resistant weed management programs mainly to glyphosate and acetolactate synthase (ALS) inhibitors has been successful. However, the information on the environmental behavior of this herbicide is limited, even more restricted when it refers to the lowland areas where problems are frequently observed regarding the selectivity of sulfentrazone, due to the soil and climatic peculiarities of this environment. In this context, the present review aims to describe the main characteristics of sulfentrazone to its environmental dynamics.